Strategies for Productive Zakat Management to Improve the Well-being of Mustahik at Baznas in Padangsidimpuan City - Mita Medina Dalimunthe; Darwis Harahap; Sarmiana Batubara (Islamic Circle, 2026)
Poverty remains one of the major socio-economic challenges in Indonesia, including in Padangsidimpuan City. Productive zakat has significant potential as an Islamic social finance instrument to empower beneficiaries (mustahik) and improve their economic welfare sustainably. However, its implementation continues to face several challenges, including the predominance of consumptive zakat distribution, limited public awareness of zakat obligations, and insufficient productive zakat funds. This study aims to analyze the management strategies of productive zakat, identify the obstacles encountered in its implementation, and evaluate its effectiveness in improving the welfare of mustahik at the National Zakat Agency (BAZNAS) of Padangsidimpuan City. This research employed a qualitative descriptive approach. Data were collected through observations, in-depth interviews, and documentation, and analyzed using data reduction, data display, conclusion drawing, and NVivo software. The study is grounded in George R. Terry's management theory, encompassing planning, organizing, actuating, and controlling, combined with the concept of productive zakat as an instrument for economic empowerment. The findings indicate that productive zakat management has been implemented through business capital assistance, provision of production facilities, mentoring, and continuous monitoring. These programs have contributed to increasing beneficiaries' income, economic independence, and overall welfare. Nevertheless, the program's effectiveness remains constrained by limited productive funds, low participation of muzakki, and the need for stronger collaboration and sustainable mentoring to achieve optimal empowerment outcomes. This study contributes to the literature on Islamic social finance by proposing a productive zakat management framework based on George R. Terry's management functions and providing practical recommendations to strengthen productive zakat governance in supporting sustainable economic empowerment of beneficiaries